Analisis E-WOM, Brand Image, Trust dan Online Purchase Intention terhadap Aplikasi Gojek - Tara Diva Azura; Tarandhika Tantra (IPM2KPE, 2024)
This research wants to find out whether Trust and Brand Image can act as mediators between E-WOM and OPI in the Gojek Application. The research method used is quantitative, with data collection through questionnaires using a Likert scale. A total of 385 respondents who had used the Gojek Application service were selected using a purposive sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) with the help of SMART PLS 3 software. The research results show that E-WOM has a positive and significant influence on Trust and Brand Image. The influence of Brand Image on Trust is also significant. In the Intervening test, only Brand Image moderated the influence of E-WOM on Trust. Brand Image plays a key role in creating a big influence on Trust. In conclusion, Gojek is advised to continue to innovate in application development in order to build a positive image for its consumers. The better Gojek's image, the greater consumer confidence in using the services offered through the Gojek Application. Keywords: Gojek Application, Brand Image, E-Wom, Online Purchase Intention, Trust